2015
DOI: 10.1590/s0100-736x2015000800008
|View full text |Cite
|
Sign up to set email alerts
|

Ramos colaterais do Arco aórtico do preá (Galea spixii Wagler, 1831)

Abstract: RESUMO.-O preá é um roedor típico da caatinga pertencente à família Caviidae. Considerando a inexistência de dados sobre o arco aórtico do preá, foi realizado este estudo tendo como objetivo descrever os ramos colaterais do arco aórtico neste cavídeo, e dessa forma, contribuir com dados para biologia da espécie. Foram utilizados vinte preás machos provenientes de estudos anteriores e encontravamse armazenados em freezer no Centro de Multiplicação de Animais Silvestres (CEMAS/UFERSA). Os animais foram descongel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In the second pattern, two branches (a trunk common to the brachiocephalic trunk and the left common carotid artery) formed the trunk described as brachiocarotid in this study, as well as the left subclavian artery. A similar pattern has been described in the galea (Oliveira et al., 2015) and the giant anteater. In the third and less common pattern, a single branch, namely the bibrachiocephalic trunk, stemmed from the aorta and gave rise to both brachiocephalic trunks.…”
Section: Discussionsupporting
confidence: 84%
“…In the second pattern, two branches (a trunk common to the brachiocephalic trunk and the left common carotid artery) formed the trunk described as brachiocarotid in this study, as well as the left subclavian artery. A similar pattern has been described in the galea (Oliveira et al., 2015) and the giant anteater. In the third and less common pattern, a single branch, namely the bibrachiocephalic trunk, stemmed from the aorta and gave rise to both brachiocephalic trunks.…”
Section: Discussionsupporting
confidence: 84%
“…The right common carotid artery and left and right subclavian arteries emerge from the brachiocephalic trunk. This arrangement was reported in the southern‐fur‐seal ( Arctocephalus australis ; Guimarães, Mari, Le Bas, & Watanabe, ), while in the majority of terrestrial species studied, it predominated in rodents such as the paca ( Agouti paca ; Oliveira, Machado, Miglino, & Nogueira, ), long‐tailed chinchilla ( Chinchilla lanigera ; Araújo, Oliveira, & Campos, ; Özdemir, Çevik‐Demirkan, & Türkmenoğlu, ), guinea‐pig ( Cavia porcellus ; Kabak & Haziroglu, ), rock cavy ( Kerodon rupestris ; Magalhães, Albuquerque, Oliveira, Papa, & Moura, ), coypu ( Myocastor coypus ; Campos, Araújo, & Azambuja, ) and the spix's yellow‐toothed cavy ( Galea spixii ; Oliveira et al, ).…”
Section: Discussionmentioning
confidence: 63%
“…In some species of terrestrial mammals such as the European brown hare ( Lepus europaeus ; Brudnicki, Macherzyńska, & Nowicki, ), the rock cavy (Magalhães et al, ), pig ( Sus scrofa domesticus ; Konig & Liebich, , p. 788) and the southern tamandua ( Tamandua tetradactyla ; Pinheiro, Lima, Pereira, Gomes, & Branco, ), a common trunk is observed which creates the right and left common carotid arteries, called a bicarotid trunk. This arrangement is a standard structure in these species, but it can be observed in other species of animals as a variation, for example in 10% of spix's yellow‐toothed cavy (Oliveira et al, ). This structure was not observed in manatees, since in these animals, the left common carotid artery arises directly from the aortic arch, making it impossible to approach the right common carotid artery in the brachiocephalic trunk.…”
Section: Discussionmentioning
confidence: 93%
“…Oliveira, Costa, et al (2020), gathered several studies on these groups of animals, and framed them in three different types of vascular arrangements, comprising types 1, 2 and 3. The vascular distribution arrangement in the collared peccary, from which the brachiocephalic trunk and the left subclavian artery arose directly from the aortic arch, has also been reported for other wild animals, such as the white-eared opossum (Didelphis albiventris) (Reckziegel et al, 2003), ocelot (Leopardus pardalis) (Martins et al, 2010), nutria (Myocastor coypus) (Campos et al, 2010), European rabbit (Oryctolagus cuniculus) (Souza et al, 2013), Spix's yellowtoothed cavy (Galea spixii) (Oliveira, Oliveira, Barbosa, et al, 2015; and crab-eating fox (Cerdocyon thous) (Lima et al, 2016), as well as in the domestic pig (Susscrofa domesticus) (Lima et al, 2016). Albuquerque et al (2003), when studying the aortic arch of collared peccary foetuses, reported this same pattern, while, on the other hand, demonstrating that the brachiocephalic trunk gives rise to the right subclavian artery and the bicarotid trunk in five dissected foetuses.…”
Section: Discussionmentioning
confidence: 64%
“…Anatomical structures, arteries and organs names followed the International Committee on Gross Veterinary Anatomical Nomenclature (ICVGAN)(, 2017), except for brachiocarotid trunk that was adopted from Culau et al (2007), Oliveira, Oliveira, Bezerra, and and Oliveira, Oliveira, Barbosa, et al (2015), and our data were compared with related studies performed on domestic and wild mammals.…”
Section: Anatomical Nomenclaturementioning
confidence: 99%